Ellipsometric study of Si1-x Gex alloy - Paiman, Suriati; Sakrani, Samsudi; Ismail, Bakar; Talib, Zainal Abidin (Malaysian Solid State Science and Technology Society, 2003)
A report on ellipsometric studies of Si0.5 Ge0.5 and Si0.7 Ge0.3 thin films is described. The samples were earlier prepared from SiGe disks of 3” diameter using RF magnetron sputtering and the films were deposited onto glass substrates at room temperature. Some of the optical properties were investigated using an ellipsometer. In this method, we investigate the changes in refractive indices, n and extinction coefficients, k with film thickness as well as the relevant dielectric constant, ε. The results showed that, at a wavelength of 632.80 nm, n was found to increase with an increase of the germanium contents.